ANALISIS KINERJA SALES DEPARTMENT PT TRAKINDO UTAMA AREA NORTHERN KALIMANTAN - Hendrawan, Yudhi; yuliani, Tutik; Yusuf, Tamzil; Agus, Muhamad (Fakultas Ekonomi Universitas Balikpapan, 2023)
The purpose of this study was to determine the effect of the Incentive, Motivation, and Work Environment variables on the performance of the Sales Department of PT Trakindo Utama Area, North Kalimantan. The type of research used is quantitative research with data collection methods through questionnaires. The population in this study were all employees of the Sales Department of PT Trakindo Utama Area, North Kalimantan. In this study, a purposive sampling technique was used where the researcher only used sales employees as a sample, totaling 44 people. Methods of data analysis in this study using multiple linear regression analysis, hypothesis testing, and the coefficient of determination. The results showed that the Incentives, Motivation, and Work Environment variables had a significant effect on sales performance. Partially, the Incentive, Motivation, and Work Environment variables have a positive and significant effect on the work performance of the Sales Department of PT Trakindo Utama Area, North Kalimantan